Saindo das sombras: classe e raça na São Paulo pós-abolição (1887-1930) - Rocha, Fabio Dantas [UNIFESP] (2019)
The main subject of the present master's thesis is the analysis of the class experiences of the black population of São Paulo between 1890 and 1930. For that it was necessary to understand what the ideological patterns informed their actions and the contexts of conflicts between them and white and poor populations. By examining these experiences, it was possible to understand that the years of the First Republic in São Paulo were related to a process of official construction of a Paulista identity based on the white presence in the city. And that this process, besides constantly reformulating during the republican years, inherited ideological patterns informed by the years of the slave institution's disorganization.